Optimal dietary sequence in a nursery-phase feeding program for segregated early-weaned (9±1 d of age) pigs - Owen, K.Q.; Kats, L.J.; Richert, B.T.; Dritz, Steven S.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred forty weanling pigs (initially 7.2 lb BW and 9 + 1 d of age) were used to compare four dietary sequences of three diets in a 21-d growth trial. Diet A was formulated to contain 1.7% lysine and contained 7.5% spray-dried porcine plasma and 1.75% spray-dried blood meal. Diet B was formulated to contain 1.4% lysine and contained 2.5% spray-dried porcine plasma and 2.5% spray-dried blood meal. Diet C was formulated to contain 1.25 % lysine and contained 2.5% spray-dried blood meal. The four dietary sequences were as follows AAB, AAC, ABB, and ABC, with each letter indicating the diet fed from d 0 to 7, d 7 to 14, and d 14 to 21 postweaning, respectively. Pigs fed diet B from d 7 to 14 postweaning had numerically lower average daily gain (ADG) than pigs remaining on diet A. However, pigs fed diet B from d 14 to 21 postweaning had higher ADG compared to pigs fed diet C. Pigs fed dietary sequences AAB or ABB were 11% heavier on d 21 postweaning than pigs fed dietary sequences AAC or ABC. In conclusion, dietary sequences AAB and ABB provided identical performance from d 0 to 21 postweaning; however, utilization of a transition diet (B) from d 7 to 14 postweaning substantially reduced feed cost per lb of gain for pigs weaned at 9 d of age.
Keywords: Swine; Starter; Performance; Diet sequence